2015
DOI: 10.1002/2015gl066887
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear local parallel acceleration of electrons through Landau trapping by oblique whistler mode waves in the outer radiation belt

Abstract: Simultaneous observations of electron velocity distributions and chorus waves by the Van Allen Probe B are analyzed to identify long‐lasting (more than 6 h) signatures of electron Landau resonant interactions with oblique chorus waves in the outer radiation belt. Such Landau resonant interactions result in the trapping of ∼1–10 keV electrons and their acceleration up to 100–300 keV. This kind of process becomes important for oblique whistler mode waves having a significant electric field component along the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
132
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 61 publications
2
132
0
Order By: Relevance
“…The energization of electrons trapped into the Landau resonance requires some energy source supporting TDS propagation to sufficiently high latitudes. A similar question about energy sources has been previously raised for large‐amplitude whistler waves observed in the outer radiation belt [ Cattell et al , ; Cully et al , ; Kellogg et al , ; Wilson et al , ] and capable of providing fast energization of electrons trapped into the Landau or cyclotron resonances [ Trakhtengerts et al , ; Agapitov et al , , ; Osmane et al , ]. Shklyar [] has shown that whistler wave energy is insufficient to provide transport of resonant trapped electrons to 30°–40° latitude, where whistlers are still observed [ Cattell et al , ; Kellogg et al , ; Agapitov et al , ].…”
Section: Introductionmentioning
confidence: 80%
“…The energization of electrons trapped into the Landau resonance requires some energy source supporting TDS propagation to sufficiently high latitudes. A similar question about energy sources has been previously raised for large‐amplitude whistler waves observed in the outer radiation belt [ Cattell et al , ; Cully et al , ; Kellogg et al , ; Wilson et al , ] and capable of providing fast energization of electrons trapped into the Landau or cyclotron resonances [ Trakhtengerts et al , ; Agapitov et al , , ; Osmane et al , ]. Shklyar [] has shown that whistler wave energy is insufficient to provide transport of resonant trapped electrons to 30°–40° latitude, where whistlers are still observed [ Cattell et al , ; Kellogg et al , ; Agapitov et al , ].…”
Section: Introductionmentioning
confidence: 80%
“…Electron acceleration through Landau resonance by the parallel electric field of highly coherent oblique whistler mode waves was first considered by Artemyev et al [], who showed that it could lead to tens of keV acceleration in 100 ms for electrons with 50–100 keV initial energy. Recent Van Allen Probes observations provide evidence for the occurrence of such fast, nonlinear acceleration of radiation belt electrons with energies of 20–100 keV [ Agapitov et al , ]. To account for this additional source of electron energization, we obtain both the instantaneous frequency from the zero crossings of the E ∥ wave and the instantaneous wave amplitude E ∥ from the maximum E ∥ between zero crossings.…”
Section: Nonlinear Electron Acceleration In Vlf Riser Subpacketsmentioning
confidence: 99%
“…We then separately apply subpacket analysis to E ∥ to calculate the Landau resonance acceleration efficiency for nonlinear trapping in the parallel electric field of the chorus wave, using the expression Δ1emELandau1em(eV)=[]0.51emJ0(β)1em||boldE1emVp1emVg1emδt()VgVp1(Vg1emVp)/c21. Similar to the perpendicular wave calculations, the total and maximum single‐subpacket energy gain for electrons in Landau resonance with the parallel component of the wave electric field are shown in Figure b. The energy range <200 keV for efficient acceleration by Landau resonance is consistent with previous studies [ Agapitov et al , ; Artemyev et al , ].…”
Section: Nonlinear Electron Acceleration In Vlf Riser Subpacketsmentioning
confidence: 99%
“…In Nunn and Omura (), resonant particle distribution functions, resonant currents, and nonlinear growth rates of oblique wave‐particle interactions are discussed, and the gyroaveraging method for electron motions interacting with oblique whistler mode waves is derived. Local nonlinear acceleration of electrons through the parallel electric field from 1–10 keV to 100–300 keV are analyzed from observations (Agapitov et al, , ). Artemyev et al () reviewed observations of oblique whistler mode waves, showing the occurrences, distributions, propagation, and damping processes, and discussed wave‐particle interactions with electrons less than 1 MeV under both quasi‐linear diffusion and nonlinear trapping models.…”
Section: Introductionmentioning
confidence: 99%